Evaluation of Acute 13-Week Subchronic Toxicity and Genotoxicity of the Powdered Root of Tongkat Ali (Eurycoma longifolia Jack). (25th August 2013) - Li, Ching-Hao; Liao, Jiunn-Wang; Liao, Po-Lin; Huang, Wei-Kuang; Tse, Ling-Shan; Lin, Cheng-Hui; Kang, Jaw-Jou; Cheng, Yu-Wen
Abstract : Tongkat Ali ( Eurycoma longifolia ) is an indigenous traditional herb in Southern Asia. Its powdered root has been processed to produce health supplements, but no detailed toxicology report is available. In this study, neither mutagenicity nor clastogenicity was noted, and acute oral LD50 was more than 6 g/kg b.w. After 4-week subacute and 13-week subchronic exposure paradigms (0, 0.6, 1.2, and 2 g/kg b.w./day), adverse effects attributable to test compound were not observed with respect to body weight, hematology, serum biochemistry, urinalysis, macropathology, or histopathology. However, the treatment significantly reduced prothrombin time, partial thromboplastin time, blood urea nitrogen, creatinine, aspartate aminotransferase, creatine phosphate kinase, lactate dehydrogenase, and cholesterol levels, especially in males (P < 0.05 ). These changes were judged as pharmacological effects, and they are beneficial to health. The calculated acceptable daily intake (ADI) was up to 1.2 g/adult/day. This information will be useful for product development and safety management.